Chelation therapy with 3, 4, 3-Li(1, 2-HOPO) after pulmonary exposure to plutonium in rats. (1st June 2023) - Grémy, Olivier; Devilliers, Karine; Miccoli, Laurent
Abstract: Internal exposure to plutonium can occur through inhalation for the nuclear worker, but also for the public if the radionuclide was released into the atmosphere in the context of a nuclear accident or terrorist attack. DieThylenetriaminePentaAcetic acid (DTPA) is currently still the only authorized chelator that can be used to decorporate internalized plutonium. The Linear HydrOxyPyridinOne-based ligand named 3, 4, 3-Li(1, 2-HOPO) remains the most promising drug candidate to replace it in the hopes of improving chelating treatment. This study aimed to assess the efficacy of 3, 4, 3-Li(1, 2-HOPO) in removing plutonium from rats exposed to the lungs, depending on the timing and route of treatment, and almost always compared to DTPA at a ten-fold higher dose used as a reference chelator. First, early intravenous injection or inhalation of 3, 4, 3-Li(1, 2-HOPO) demonstrated superior efficacy over DTPA in preventing plutonium accumulation in liver and bone in rats exposed by injection or lung intubation. However, this superiority of 3, 4, 3-Li(1, 2-HOPO) was much less pronounced with delayed treatment. In rats given plutonium in the lungs, the experiments also showed that 3, 4, 3-Li-HOPO reduced pulmonary retention of plutonium more effectively than DTPA only when the chelators were injected early but not at delayed times, while it was always the better of the two chelators when they were inhaled. Under our experimental conditions, the rapid oral administration of 3, 4, 3-Li(1, 2-HOPO) was successful in preventing systemic accumulation of plutonium, but not in decreasing lung retention. Thus, after exposure to plutonium by inhalation, the best emergency treatment would be the rapid inhalation of a 3, 4, 3-Li(1, 2-HOPO) aerosol to limit pulmonary retention of plutonium and prevent extrapulmonary deposition of plutonium in target systemic tissues. Highlights: LiHOPO is more effective than DTPA in limiting systemic plutonium deposits. Early inhalation of LiHOPO is the best strategy to limit lung retention of plutonium. The superiority of 3, 4, 3-Li(1, 2-HOPO) over DTPA decreases when treatment is delayed. Orally administered 3, 4, 3-Li(1, 2-HOPO) fails to mobilize pulmonary plutonium.